Immunotherapy in Melanoma: Role of TIGIT and LAG-3 on the antitumor immune microenvironment (2023)
Melanoma, is a malignant tumor arising from melanocytes. Given the ability of melanoma cells to inactivate lymphocytes, immunotherapy in melanoma has focused on using immune checkpoint inhibitors (ICIs) to counteract immune evasion. The lymphocyte activation gene 3 (LAG-3) and the inhibitory receptor with Ig and ITIM domains (TIGIT) with its specific ligand Nectin-4 are emerging IPCs that are expressed in T cells. Overexpression of these immunological receptors is evident in melanoma, whereby different clinical trials have developed inhibitory molecules (as proven-drugs) that leading to the joint blockage of LAG-3 and TGIT/Nectin-4. Among these inhibitory molecules are PD-1/PD-L1, whose use, in addition to leading to the reduction of tumor proliferation and invasiveness, restores the activity of T cells and increases the antitumor immune response. However, the influence of LAG-3 and TIGIT/Nectin-4 on antitumor immune activity within the tumor microenvironment in melanoma remains unclear. This review describes the role of LAG-3 and TIGIT receptors in melanoma, the status of monotherapy and combination therapy targeting these immune receptors, the influence on the antitumor immune response, and the prospects for LAG-3 targeting immunotherapy. and TIGIT/Nectin-4 in melanoma.